НАЦІОНАЛЬНО-ВИЗВОЛЬНА ВІЙНА УКРАЇНСЬКОГО НАРОДУ СЕРЕДИНИ ХVII ст.: СУЧАСНА РОСІЙСЬКА ІСТОРІОГРАФІЯ (Zaporizhzhia Historical Review, 2021)
The aim of the article is to elucidate specificity of the National liberation war in Ukrainian in the middle of XVII century in post-Soviet Russian historiography. The author stresses upon main tendencies in research of the National war, analyses the main concepts of some contemporary Russian historians. The main tendencies in investigating the National independence war in contemporary Russian historiography are: Russian historians devote much attention to international context of the war, that provoked large crisis in Central-Eastern Europe in the mid-seventeenth century; intently researched is a religious aspect, i.e. the role of the Orthodox church in formation of the foreign policy of Moscow tsar, religious backgrounds of diplomatic negotiations during the war. Author comes to a conclusion that in the contemporary Russian historiography an integral conception of Ukrainian National independence war was formulated.